SPT6 recruits SND1 to co‐activate human telomerase reverse transcriptase to promote colon cancer progression. Issue 4 (12th January 2021) - Diao, Chaoliang; Guo, Ping; Yang, Wenjing; Sun, Yao; Liao, Yina; Yan, Yue; Zhao, Anshi; Cai, Xin; Hao, Jiaojiao; Hu, Sheng; Yu, Wendan; Chen, Manyu; et al.
Abstract : Human telomerase reverse transcriptase (hTERT) plays an extremely important role in cancer initiation and development, including colorectal cancer (CRC). However, the precise upstream regulatory mechanisms of hTERT in different cancer types remain poorly understood. Here, we uncovered the candidate transcriptional factor of hTERT in CRC and explored its role and the corresponding molecular mechanisms in regulating hTERT expression and CRC survival with an aim of developing mechanism‐based combinational targeting therapy. The possible binding proteins at the hTERT promoter were uncovered using pull‐down/mass spectrometry analysis. The regulation of SPT6 on hTERT expression and CRC survival was evaluated in human CRC cell lines and mouse models. Mechanistic studies focusing on the synergy between SPT6 and staphylococcal nuclease and Tudor domain containing 1 (SND1) in controlling hTERT expression and CRC progression were conducted also in the above two levels. The expression correlation and clinical significance of SPT6, SND1, and hTERT were investigated in tumor tissues from murine models and patients with CRC in situ. SPT6 was identified as a possible transcriptional factor to bind to the hTERT promoter. SPT6 knockdown decreased the activity of hTERT promoter, downregulated the protein expression level of hTERT, suppressed proliferation, invasion, and stem‐like properties, promoted apoptosis induction, and enhanced chemotherapeutic drug sensitivity in vitro . SPT6 silencing also led to the delay of tumor growth and metastasis in mice carrying xenografts of human‐derived colon cancer cells. Mechanistically, SND1 interacted with SPT6 to co‐control hTERT expression and CRC cell proliferation, stemness, and growth in vitro and in vivo . SPT6, SND1, and hTERT were highly expressed simultaneously in CRC tissues, both from the murine model and patients with CRC in situ, and pairwise expression among these three factors showed a significant positive correlation. In brief, our research demonstrated that SPT6 synergized with SND1 to promote CRC development by targeting hTERT and put forward that inhibiting the SPT6‐SND1‐hTERT axis may create a therapeutic vulnerability in CRC. Abstract : Colorectal cancer (CRC) is continuously rising among young adult patients, necessitating more forethoughtful study and understanding of the mechanisms behind CRC and the development of the new diagnostic and therapeutic strategies. Our research demonstrated that SPT6 synergized with staphylococcal nuclease and Tudor domain containing 1 (SND1) to promote CRC progression by targeting human telomerase reverse transcriptase (hTERT) and put forward that inhibiting SPT6‐SND1‐hTERT axis may create a therapeutic vulnerability in CRC.